Virtual monitors vs. physical monitors: an empirical comparison for productivity work - Pavanatto, Leonardo; Davari, Shakiba; Badea, Carmen; Stoakley, Richard; Bowman, Doug A. (Frontiers in Virtual Reality, 2023)
Virtual monitors can display information through a head-worn display when a physical monitor is unavailable or provides insufficient space. Low resolution and restricted field of view are common issues of these displays. Such issues reduce readability and peripheral vision, leading to increased head movement when we increase the display size. This work evaluates the performance and user experience of a virtual monitor setup that combines software designed to minimize graphical transformations and a high-resolution virtual reality head-worn display. Participants performed productivity work across three approaches: Workstation, which is often used at office locations and consists of three side-by-side physical monitors; Laptop, which is often used in mobile locations and consists of a single physical monitor expanded with multiple desktops; and Virtual, our prototype with three side-by-side virtual monitors. Results show that participants deemed Virtual faster, easier to use, and more intuitive than Laptop, evidencing the advantages of head and eye glances over full content switches. They also confirm the existence of a gap between Workstation and Virtual, as Workstation achieved the highest user experience. We conclude with design guidelines obtained from the lessons learned in this study.